PERSONALITY OR ACCULTURATION – WHAT MATTERS FOR SUBSTANCE USE OF LITHUANIAN EMIGRANTS? - Aukse Endriulaitiene; Laura Seibokaite; Aiste Pranckeviciene; Kristina Zardeckaite-Matulaitiene; Rasa Marksaityte (European Scientific Journal, ESJ, 2015)
The study aim: The current study aims to explore the predictive factors of substance use (smoking, alcohol and drug consumption) among Lithuanian emigrants living in different European countries. The interaction between personality and acculturation strategies as the predictors of emigrant substance use is investigated. The material and method: 210 Lithuanian emigrants (76 males, 134 females) living in different European countries participated in the study. They completed the self-report online questionnaire that included Big Five personality inventory, acculturative behaviour scale, seven questions about smoking, alcohol and drug use, and socio demographic questions. The main results and conclusions: Higher scores of assimilation added to the negative effect of neuroticism when predicting more problematic alcohol use of male emigrants. Whereas in the group of females only higher agreeableness predicted lower alcohol consumption. In the case of smoking agreeableness, openness and neuroticism were significant predictors for male emigrants, whereas acculturation strategies had no predictive value. The smoking of female emigrants was predicted neither by personality nor by acculturation. We supported the idea that personality traits are the most stable and informative predictors of health – risk behaviour in emigrants’ sample, although certain acculturation strategies could add some of explanatory value at least for males. Also, substance use of emigrant men and women is of different nature.